Methods and approaches of Complexity Theory and Fuzzy Logic for intensity of university research in terms of Creative Work to be estimated - Galiakhmetova, Marina Railevna; Koretskiy, Vladimir Pavlovitch; Mardanova, Irina Mikhailovna; Józsa, László (Journal of Eastern European and Central Asian Research (JEECAR), 2019)
This article describes the main approaches to research in terms of creative labor regulation and time study. Definition of a creative labor and brain-work product as a subject of regulation and work intensity estimation was developed. The method for creative brain-work intensity estimation was based on complexity theory, which enables the evaluation of the complexity of creative brain-work results and time expenditure. Because of the appropriateness of linguistic expert assessments while labor intensive creative work is carried out, the methods and approaches of fuzzy logic were suggested to assess the Competence Complexity of the creative work product. Based on statistical and expert models, a regression was built to estimate time expenditure dependence of the creative brain-work expected outcomes on Competence Complexity. The resulting dependency allows the estimation of the time spent on the research project based on the estimation of the expected project results.